Testing coyotes in an object choice task following a human gesture. Issue 4 (4th July 2021) - Floyd, Nathan; Young, Julie K.
Abstract : Interspecific communication is often studied by determining a species ability to respond to human gestures. Results emerging from pet versus free-roaming domestic dogs (C anis familiaris ) elucidate differences in the behavioral changes that occur based on life experience and human socialization in the development of social cognition. Additional research on wild species of canids raised with minimal levels of human socialization may provide insight into the importance of human socialization in the ability of non-human animals to correctly respond to a human gesture. We used captive coyotes ( Canis latrans ) to test whether coyotes could use human pointing gestures to succeed in an object-choice task. We specifically tested two groups of coyotes; both were minimal human socialization but one group was coyote-reared while the other group had high levels of human socialization during early ontogenetic development because they were hand-reared until 12 weeks of age. We tested 12 coyotes (n = 5 hand-reared, n = 7 coyote-reared) on responses to a human distal-pointing gesture across 10 trials each. Only one coyote, a hand-reared male, performed better than expected by chance and made correct choices in eight trials (incorrect choices in trials three and four). We found no difference between coyote- or hand-reared coyotes in their abilities to respond correctly to a human distal-pointing gesture (t = – 0.043, P = 0.97). Performance did not improve over time among all coyotes or within either group. The preliminary results from this study suggest that most coyotes will not respond to human gestures and early life experience does not appear to improve adult performance. These findings are in contrast to most studies of gesture studies of canids.